Sequences within and flanking hypersensitive sites 3 and 2 of the beta-globin locus control region required for synergistic versus additive interaction with the epsilon-globin gene promoter. - Jackson, J D (1996)
The locus control region is required for high-level, position-independent expression of mammalian beta-globin genes. It is marked by five major DNase hypersensitive sites (HSs) in a 16 kb region of chromatin, and the protein-DNA complexes that form these HSs may interact in a holocomplex that carries out the full function of the locus control region. Previous studies showed that a large rabbit DNA fragment containing both HS2 and HS3 in their native sequence context and spacing produced a much larger increase in expression of a linked reporter gene than the sum of the largest effects observed with DNA fragments containing HS2 or HS3 individually. To test whether this reflected a synergistic interaction between the 200-400 bp cores of the HSs or if this effect required additional sequences outside the cores, combinations of different restriction fragments containing HS2 or HS3 were tested for their ability to increase the expression of a hybrid epsilon-globin-luciferase reporter gene in transfected K562 cells. The results show that the human HS2 and HS3 cores do not interact either additively or synergistically with the reporter gene when juxtaposed, and separation by spacer DNA has little effect on their function. Fragments of human DNA containing cores plus flanking sequences for HS3 or HS2 show an additive effect in combination, whereas homologous fragments of rabbit DNA containing HS3 and HS2 interact synergistically. At least part of this difference localizes to the rabbit DNA fragment containing HS3, which can interact synergistically with the human DNA fragment containing HS2. The region 5' to the HS3 core plays a role both in the cooperative interaction observed with the rabbit DNA fragment and the domain-opening observed with the human DNA. A minor DNase HS maps to this region, and the pattern of sequence conservation is consistent with some difference in function between species.